The current state of the pharmaceutical market of Ukraine, quality assurance and falfication of medicines - Hanna Eiben; Liliia Hala; Valentyna Slipchuk (Pensoft Publishers, 2021)
The aim of our article was the study of the current state of the pharmaceutical market of Ukraine in the context of the quality assurance of medicines and preventing the spread of falsified medicines (FM), the identification of the main problems in the field of circulation of medicines and the ways to solve them. It is established that the dynamic development of the pharmaceutical market and its high profitability cause problem of drug quality, increasing threats to the spread of FM in circulation and require the implementation of effective mechanisms for regulation of quality and safety of medicines. Analysis the annual official statistics of the State Service of Ukraine on Medicines and Drug Control for the period of 2008-2019 on the number of detected FM in circulation showed a steady trend of increasing FM and insufficient implementation of effective measures to combat them. The creation of effective quality assurance system of drugs and preventing the spread of FM need to improve the organization of state control of drug quality, strengthening criminal liability for falsification of drugs and optimization of the system of their detection.